2008
DOI: 10.1258/acb.2007.007189
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sphingosine-1-phosphate measurement in healthy subjects: close correlation with red blood cell parameters

Abstract: Background: Since sphingosine-1-phosphate (Sph-1-P) plays an important role as an extracellular mediator through interaction with specific cell surface receptors, especially in the area of vascular biology and immunology/haematology, determination of its plasma concentration may become important from the clinical viewpoint. Thus, we attempted to develop a method of measuring the plasma Sph-1-P concentration for use in the clinical laboratory setting. Methods: After two-step lipid extraction, Sph-1-P was couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 39 publications
4
74
1
1
Order By: Relevance
“…Moreover, studies with ABC receptor knockout mice showed that neither ABCC1, ABCA1, nor ABCA7 contribute to plasma S1P levels (39). Nevertheless, these studies are consistent with recent findings in humans that plasma S1P levels positively correlate with erythrocyte levels (40). It has also recently been suggested that the vascular endothelium, in addition to the hematopoietic system, may also contribute to plasma S1P (37) and that ABCA1 and ABCC1 might be involved in S1P release from endothelial cells (39).…”
Section: The S1p Gradientsupporting
confidence: 84%
“…Moreover, studies with ABC receptor knockout mice showed that neither ABCC1, ABCA1, nor ABCA7 contribute to plasma S1P levels (39). Nevertheless, these studies are consistent with recent findings in humans that plasma S1P levels positively correlate with erythrocyte levels (40). It has also recently been suggested that the vascular endothelium, in addition to the hematopoietic system, may also contribute to plasma S1P (37) and that ABCA1 and ABCC1 might be involved in S1P release from endothelial cells (39).…”
Section: The S1p Gradientsupporting
confidence: 84%
“…One study showed that plasma S1P level is higher in males than in females ( 62 ), whereas another study found the opposite in both mice and humans ( 63 ). However, other authors did not observe any gender difference ( 52,56 ).…”
Section: Plateletsmentioning
confidence: 96%
“…We therefore investigated the impact of apoM on two other potential pathways of S1P metabolism, namely effl ux from erythrocytes and urinary excretion. Plasma concentrations of S1P were recently shown to correlate with red blood cell counts ( 5,6,14 ), probably because the lack of the S1P-degrading lyase makes erythrocytes the main source of S1P in plasma ( 4,5 ). Because HDL was previously found to induce S1P effl ux from erythrocytes ( 5 ), we compared the S1P effl ux capacity of HDL from wild-type (wt), Apom…”
Section: S1p Effl Ux From Erythrocytesmentioning
confidence: 99%